2240 W high-brightness 1018 nm fiber laser for tandem pump application. (23rd November 2017) - Li, Ruixian; Xiao, Hu; Leng, Jinyong; Chen, Zilun; Xu, Jiangming; Wu, Jian; Zhou, Pu
Abstract: In this letter, we present a 2240 W high-brightness 1018 nm fiber laser by power combination. The system consists of seven 1018 nm ytterbium-doped fiber lasers and a homemade 7 × 1 all-fiber power combiner. The output core diameter of the power combiner is 50 µ m and the numerical aperture is 0.2. The overall transmission efficiency is about 99%. This high-power, high-brightness fiber laser can be used as a pump source in tandem pumping configurations for several kilowatts of power scaling.